(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to analyze the impact of integration between marketing and management on improving the quality of decision-making within small and medium-sized enterprises (SMEs) in Libya. It examined the relationship between information sharing, joint planning, and the implementation of activities between the two departments. The study adopted a descriptive-analytical approach, and data were collected באמצעות a questionnaire distributed to a random sample of 50 employees working in SMEs. The data were analyzed using SPSS software. The results indicated a high level of reliability and validity of the measurement instrument. They also revealed a strong, statistically significant positive correlation between the dimensions of integration between marketing and management and the quality of decision-making. Furthermore, the findings showed that the level of integration between marketing and management was moderate, with some relative weaknesses in certain aspects, particularly in continuous coordination between top management and the marketing department. The hypothesis testing results confirmed the presence of a statistically significant effect of integration in information sharing, strategic planning, and activity implementation between marketing and management on the quality of decision-making within the studied organizations. The study recommended enhancing integration among different departments, developing decision support systems, and increasing reliance on marketing information in decision-making processes, thereby contributing to improved organizational performance efficiency and increased competitiveness of SMEs